Firm response to competitive shocks: Evidence from China's minimum wage policy - Harald Hau; Yi Huang; Gewei Wang (Graduate Institute of International and Development Studies, 2016)
The large regional variation of minimum wage changes in 2002-08 implies that Chinese manufacturing firms experienced competitive shocks as a function of firm location and their low-wage employment share. We find that minimum wage hikes accelerate the input substitution from labor to capital in low-wage firms, reduce employment growth, but also accelerate total factor productivity growth-particularly among the less productive firms under private Chinese or foreign ownership, but not among state-owned enterprises. The heterogeneous firm response to labor cost shocks can be explained by differences in governance or management practice, but is difficult to reconcile with the idea that competitive pressure is a substitute for governance quality.
Keywords: D24; G31; J24; J31; O14; 330; firm productivity; capital investment; minimum wage policy